1994
DOI: 10.1161/01.res.74.2.310
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of coronary collateral vasoconstriction in response to cyclooxygenase blockade.

Abstract: The present study was performed to examine the mechanism by which cyclooxygenase blockade produces vasoconstriction in well-developed coronary collateral vessels. Eight dogs were studied 4 to 6 months after occlusion of the left anterior descending coronary artery (LAD) had been performed to stimulate collateral vessel growth. At the time of study, the LAD was cannulated at the site of occlusion for measurement of retrograde blood flow as an index of collateral blood flow. Levels of 6-ketoprostaglandin F,a wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…PGI 2 that led to great increases of blood flow to the myocardium. This confirms in the rat, in vivo , the coronary vasodilation described in vitro as well as that reported in other animal species ( Moncada & Vane, 1979 ) and reinforced the hypothesis for a physiological role of PGI 2 ( Altman & Bache, 1994 ), which is the major prostaglandin produced in the rat heart ( De Deckere et al ., 1977 ). PGI 2 decreases heart work in anaesthetized cats ( Lefer et al ., 1978 ).…”
Section: Discussionsupporting
confidence: 88%
“…PGI 2 that led to great increases of blood flow to the myocardium. This confirms in the rat, in vivo , the coronary vasodilation described in vitro as well as that reported in other animal species ( Moncada & Vane, 1979 ) and reinforced the hypothesis for a physiological role of PGI 2 ( Altman & Bache, 1994 ), which is the major prostaglandin produced in the rat heart ( De Deckere et al ., 1977 ). PGI 2 decreases heart work in anaesthetized cats ( Lefer et al ., 1978 ).…”
Section: Discussionsupporting
confidence: 88%
“…Some centres, such as Lund, have changed the treatment regime to ibuprofen. However, one study on dogs showed reduced flow in coronary collaterals after ibuprofen injection (20). Other studies suggest that the ibuprofen has less influence on flow and perfusion of organs as compared to IND.…”
Section: Discussionmentioning
confidence: 99%